Generalized Symmetric (f,g) – Biderivations on Lattices - Karim, Mazen (JOURNAL OF ADVANCES IN MATHEMATICS, 2020)
In this paper, we introduce the notion of generalized symmetric -derivations on lattices, also some properties of generalized symmetric - derivations we studies.